2009
DOI: 10.1016/j.juro.2009.02.104
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Bladder Oxidative Stress and Inflammation by a Phytotherapeutic Agent in a Rat Model of Partial Bladder Outlet Obstruction

Abstract: Eviprostat mediated decrease of the increased oxidative stress and bladder inflammation caused by bladder outlet obstruction may contribute to the protection of bladder function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
88
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(100 citation statements)
references
References 14 publications
9
88
2
1
Order By: Relevance
“…The changes in the bladder weight after pBOO were consistent with the changes seen in previous studies (2, 3, 21,22,30). pBOO clearly induced time-dependent increases in bladder weight that continued until day 7; these increases seemed to reach a plateau by day 14 after pBOO.…”
Section: Discussionsupporting
confidence: 90%
“…The changes in the bladder weight after pBOO were consistent with the changes seen in previous studies (2, 3, 21,22,30). pBOO clearly induced time-dependent increases in bladder weight that continued until day 7; these increases seemed to reach a plateau by day 14 after pBOO.…”
Section: Discussionsupporting
confidence: 90%
“…But, Shabsigh et al reported castration resulted in a rapid and significant reduction of blood flow to the rat ventral prostate gland that was not seen in the bladder [11]. In this results, bladder contractile forces in response to EFS (2,8, and 32 Hz), carbachol and KCl did not change in NBP rats. These results indicated the bladder function is not influenced in this NBP model.…”
Section: Discussionmentioning
confidence: 50%
“…Contractile responses were measured as described by Oka et al [8]. The bladder dome was removed and full-thickness longitudinal strips of about 3 × 10 mm were taken from the bladder body.…”
Section: Contractility Measurements In Isolated Bladder Smooth-musclementioning
confidence: 99%
“…The histological examination of the BOO rat bladder showed that there was infiltration of inflammatory cells in the bladder, including mast cells. BOO causes ischemic reperfusion and oxidative stress within the bladder, which can then induce bladder inflammation (26,35). Previous studies have demonstrated that ischemia and inflammation cause platelet activation and the release of 5-HT (34,37).…”
Section: Discussionmentioning
confidence: 99%